2013
DOI: 10.2174/157015913804999540
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immunity and the Inflammatory Response: A New Target for Treating Drug-resistant Epilepsy

Abstract: Until recently, epilepsy medical therapy is usually limited to anti-epileptic drugs (AEDs). However, approximately 1/3 of epilepsy patients, described as drug-resistant epilepsy (DRE) patients, still suffer from continuous frequent seizures despite receiving adequate AEDs treatment of sufficient duration. More recently, with the remarkable progress of immunology, immunity and inflammation are considered to be key elements of the pathobiology of epilepsy. Activation of inflammatory processes in brain tissue has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 157 publications
0
13
0
2
Order By: Relevance
“…Increased staining for HMGB1, TLR4 and RAGE, is detectable in an analogous pattern to that observed in mouse models of epilepsy in human hippocampal tissue obtained at surgery from patients with (2). Inflammasome formation induces caspase-1 activation (3).…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 87%
“…Increased staining for HMGB1, TLR4 and RAGE, is detectable in an analogous pattern to that observed in mouse models of epilepsy in human hippocampal tissue obtained at surgery from patients with (2). Inflammasome formation induces caspase-1 activation (3).…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 87%
“…Recent studies have indicated that inflammation probably plays a crucial role in the development of DRE [ 32 35 ]. Moreover, inflammatory modulation could improve seizure control in some patients with DRE [ 34 , 35 ], which supports the hypothesis of an inflammatory mechanism of DRE and suggests a new strategy for drug resistance. Interestingly, this study found that the AA genotype at rs4817027 and the CC haplotype (rs987195-rs969885) were genetic susceptibility markers for DRE but the CG haplotype (rs987195-rs969885) was a genetic protective factor against DRE.…”
Section: Discussionmentioning
confidence: 63%
“…ii) Factors affecting neural cell membrane stability: after stroke, neural cell membrane instability can give rise to abnormalities in the function of surrounding cells and selective neuronal mutations, leading to an increase in neural cell excitability and synchronous discharge, thus resulting in epilepsy ( 9 ). iii) Inflammatory factors: after stroke, long-term inflammatory responses can generate changes in morphology, increasing the amount of neuroglia, thus causing or aggravating epilepsy ( 10 ). iv) Immunological factors: Disorders in immunological functions have been found in EAS patients, including abnormal humoral and cellular immunological functions, which can induce the onset of epilepsy ( 11 ).…”
Section: Discussionmentioning
confidence: 99%